Sport and Contested Identities : Contemporary Issues and Debates - Acton, Ciaran; Hassan, David (London : Taylor and Francis, 2018)
Identity is one of the most theorised and contested of all sociological concepts and sport is fertile ground for an examination of its complexities. This book offers a wide-ranging and up-to-date exploration of the sport-identity nexus, drawing examples from a variety of sporting contexts and geographical locations, and incorporating a diversity of perspectives including players, spectators, officials, the media and policy-makers. Covering key themes in the social scientific study of sport such as gender, ethnicity and national identity, it considers the impact of social, cultural and technological change on the formation of sporting identities. Including original real-life case studies, each chapter makes a unique contribution to our understanding of the complex relationship between sport and identity. As this relationship is embedded within the broader structures of power that frame social inequality, this book also poses important questions about the role of sport-related initiatives in our society today, as well as in years to come. Sport and Contested Identities: Contemporary Issues and Debates is fascinating reading for all students and scholars of the sociology of sport.
chapter Introduction: Sport and contested identities / CIARAN ACTON -- part PART 1 Participation -- chapter 1 The under- representation and racialized experiences of minority coaches in high level coach education in professional football in England / STEVEN BRADBURY -- chapter 2 The Good Friday dis- agreement: sport and contested identities in Northern Ireland since 1998 / CONOR MURRAY -- part PART 2 Spectators and supporters -- chapter 3 Enemies at play: contested identities in India- Pakistan cricket / KAUSIK BANDYOPADHYAY -- chapter 4 British Asians and football: exploring the rise, popularity and significance of Punjabi and Bangla fan groups / DANIEL KILVINGTON -- part PART 3 Media representations -- chapter 5 Football and race talk among Dutch football media audiences / JACCO VAN STERKENBURG AND DENNIS BLOKZEIJL -- chapter 6 A level playing field: gender, sexuality and exclusion in sport / TERESA WILLIS -- r
Keywords: Sports -- Sociological aspects; Identity (Psychology)